Music That Moves You: Auditory Vection Induced by the Shepard-Risset Glissando - Mursic, Rebecca; Riecke, Bernhard E.; Apthorp, Deborah; Palmisano, Stephen (44th Annual Conference of the Australasian Society for Experimental Psychology (EPC), 2017)
Sounds are thought to contribute to perceptions of self-motion, often via higher-level, cognitive mechanisms. This study examined whether illusory self-motion (i.e. vection) could be induced by auditory metaphorical motion stimulation (without providing any low-level sensory information consistent with self-motion). Five different types of auditory stimuli were presented to our 20 blindfolded, stationary participants (via a surround-sound loud speaker array): (1) an ascending Shepard-Risset glissando; (2) a descending Shepard-Risset glissando; (3) a combined Shepard-Risset glissando; (4) a combined-adjusted (loudness-controlled) Shepard-Risset glissando; and (5) a white-noise control stimulus. We found that compelling auditory vection was induced by all four Shepard-Risset Glissandi compared to the white-noise control. This metaphorical auditory vection appeared similar in strength to the vection induced by the visual (physics-based) reference stimulus. Replicating past visual vection findings, we also found that individual differences in postural instability appeared to significantly predict auditory vection magnitude ratings. These findings are consistent with the notion that auditory contributions to self-motion perception may be predominantly due to higher-level cognitive factors (Väljamäe & Sell, 2014).
Keywords: Riecke; Riecke_2017; bernhard-riecke; deborah-apthorp; posterWithoutPaper; rebecca-mursic; stephen-palmisano; talkWithoutPaper